Isoxazol-5(2H)-one: a new scaffold for potent human neutrophil elastase (HNE) inhibitors - Vergelli C. Claudia; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Crocetti L. Letizia; Iacovone A. Antonella; Giovannoni M. P. Maria Paola; Guerrini G. Gabriella; Khlebnikov A. I. Andrey Ivanovich; Ciattini S. Samuele; Ciciani G. Giovanna; Quinn M. T. Mark (2017, 2017)
Title screen